Non-regular work: trends, labour law policy, and industrial relations developments - The case of Japan - Hamaguchi, Keiichiro; Ogino,Noboru (Geneva, 2011)
"Overview of recent developments in the economy and labour markets and the trends in non-regular employment -- Policy developments concerning non-regular employment and tripartite dialogue processes -- Non-regular employment: industrial relations developments and good practices."